Foundations of the psychological intervention : a unifying theoretical and methodological framework - Salvatore, Sergio; Cordella, Barbara (London : Routledge, 2024)
Foundations of the Psychological Intervention presents a new General Theory for Psychological Intervention (GTPI), delving into how its methodology can be applied across diverse psychological contexts. Rooted in semiotic cultural psychology and guided by the GTPI framework, this book offers a cohesive perspective of psychology, addressing the prevailing fragmentation evident in various domains of psychology such as health, sports, forensic, organisational, and clinical psychology. The framework establishes a foundation of methods and techniques that render psychological interventions applicable across various domains, substantiated by concrete examples from different areas. With chapters revolving around theories of action, change and the client dynamics, this groundbreaking work provides both a conceptual and methodological structure to underpin domain-specific theories and methodologies, thereby strengthening the conceptual links among distinct domains of psychology. As one of the first works to develop a theory and method of intervention across multiple psychological domains, this book will be of interest to postgraduate students and researchers specialising in cultural psychology, clinical psychology, health psychology, and the philosophy of psychology. Moreover, it serves as a useful reading for practising psychologists and psychology professionals.
Introduction1. The General Theory of Psychological Intervention2. Theory of The Object3. Theory of The Chnage4. Theory of The Action5. Theory of The Client6. Levels of the Intervention
Keywords: Psychotherapy; PSYCHOLOGY / General; PSYCHOLOGY / Applied Psychology; PSYCHOLOGY / Research & Methodology